2003
DOI: 10.1038/sj.gt.3301954
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral gene transfer into fetal mouse livers (a comparison between the cationic polymer PEI and naked DNA)

Abstract: We investigated the efficacy and safety of the cationic polymer polyethylenimine (PEI) as a potential tool for intrauterine gene delivery into livers of fetal mice in the last trimester of pregnancy (E17.5). Using luciferase as a reporter gene, transferrin-conjugated and ligand-free PEI/ DNA complexes (containing 3 mg DNA) with varying PEInitrogen/DNA-phosphate (N/P) ratios and different PEI forms, branched (800, 25 kDa) and linear (22 kDa), were compared with naked DNA. Transgene expression was measured 48 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 33 publications
(44 reference statements)
1
22
0
1
Order By: Relevance
“…Gharwan and colleagues reported that the gene transfer efficacy of naked DNA was approximately 40 times higher in fetuses than in adults, indicating that fetal tissue is especially amenable to the uptake and expression of naked DNA. 55 This result supports both our hypothesis that stem cells subjacent to a full-thickness lesion are likely amenable to taking up naked DNA and expressing our protein to augment repair, as well as the concept of using naked DNA combined with a cationic carrier such as collagen for efficient transient gene delivery.…”
Section: Discussionsupporting
confidence: 76%
“…Gharwan and colleagues reported that the gene transfer efficacy of naked DNA was approximately 40 times higher in fetuses than in adults, indicating that fetal tissue is especially amenable to the uptake and expression of naked DNA. 55 This result supports both our hypothesis that stem cells subjacent to a full-thickness lesion are likely amenable to taking up naked DNA and expressing our protein to augment repair, as well as the concept of using naked DNA combined with a cationic carrier such as collagen for efficient transient gene delivery.…”
Section: Discussionsupporting
confidence: 76%
“…The toxicity that arises with PEI administration is associated with charged PEI-pDNA nanoparticles interacting with blood components such as erythrocytes, causing aggregation in the lung capillaries and subsequent lung embolism. [34,58,59] Injecting PEI-pDNA nanoparticles intravenously or intratracheally results in gene expression that is stronger in the lung than liver, heart, spleen or kidneys. [30,34] Because the peritoneal cavity acts as barrier to PEI-pDNA nanoparticles entering the lung or bypassing the blood-brain barrier, PEI-pDNA nanoparticles injected via this route are expected to demonstrate significantly reduced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Polyethylenimine (PEI) is currently the most popular polymer used to deliver genes into various cell types [10][11][12][13], including neurons [10,11]. PEI is able to condense genes into small nanoparticles [14] and protect the DNA from degradation by nucleases [15].…”
Section: Introductionmentioning
confidence: 99%